Pengaruh Lingkungan Kerja, Beban Kerja Dan Etos Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Duta Abadi Primantara Jakarta - Andini Elvatiana; Laksono Edhi Lukito; Imas Sukaesih (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to determine the effect of the work environment, workload and work ethic on the work productivity of PT. Duta Abadi Primantara Jakarta for Sales Promoter. The type of research used is quantitative method research. The sampling technique uses the saturated sample technique, which is to take the entire population to be sampled. The sample used 74 respondents. The methods of data collections using interview and questionnaire. The data analysis technique using application of IBM SPSS version 25. This study proves that (1) there is a significant effect of the work environment on employee work productivity, (2) there is a significant effect of workload on employee work productivity, (3) there is a significant effect of work ethic on employee work productivity, and (4) work environment, workload and work ethic together have a significant effect on employee productivity at PT. Duta Abadi Primantara.